Contamination status of lipophilic marine toxins in shellfish samples from the Bohai Sea, China. (June 2019) - Liu, Yang; Yu, Ren-Cheng; Kong, Fan-Zhou; Li, Chen; Dai, Li; Chen, Zhen-Fan; Geng, Hui-Xia; Zhou, Ming-Jiang
Abstract: Lipophilic marine toxins in shellfish pose significant threats to the health of seafood consumers. To assess the contamination status of shellfish by lipophilic marine toxins in the Bohai Sea, nine species of shellfish periodically collected from five representative aquaculture zones throughout a year were analyzed with a method of liquid chromatography-tandem mass spectrometry (LC–MS/MS). Lipophilic marine toxins, including okadaic acid (OA), dinophysistoxin-1 (DTX1), pectenotoxin-2 (PTX2), yessotoxin (YTX), homo-yessotoxin (homo-YTX), azaspiracids (AZA2 and AZA3), gymnodimine (GYM), and 13-desmethyl spirolide C (13-DesMe-C), were detected in more than 95 percent of the shellfish samples. Toxins PTX2, YTX, 13-DesMe-C and GYM were predominant components detected in shellfish samples. Scallops, clams and mussels accumulated much higher level of lipophilic marine toxins compared to oysters. Toxin content in shellfish samples collected from different sampling locations showed site-specific seasonal variation patterns. High level of toxins was found during the stages from December to February and June to July in Hangu, while from March to April and August to September in Laishan. Some toxic algae, including Dinophysis acuminata, D. fortii, Prorocentrum lima, Gonyaulax spinifera and Lingulodinium polyedrum, were identified as potential origins of lipophilic marine toxins in the Bohai Sea. The results will offer a sound basis for monitoring marine toxins and protecting the health of seafood consumers. Graphical abstract: Image 1 Highlights: Shellfish samples were monthly collected from aquaculture zones in the Bohai Sea. Lipophilic phycotoxins in shellfish were analyzed using HPLC-MS/MS combined with SPE. Lipophilic phycotoxins could be detected in 104 out of 110 shellfish samples. PTX2, YTX, SPX1 and GYM were predominated in shellfish samples from the Bohai Sea. Scallop, clam and mussel were easily contaminated by lipophilic phycotoxins. Abstract : A wide array of lipophilic marine toxins were detected in shellfish samples from the Bohai Sea, which constitute an emerging pollution issue in this region.